Multi-wavelength observations of sprites over southern Africa - Nnadih, Stanislaus Ogechukwu (Department of Electrical Engineering, 2020)
Sprites are short-lived, optical upper atmospheric lightning-induced phenomena that occur above an active thunderstorm, at an altitude range of 40 - 85 km. They are often described as electrical discharges in the mesosphere, following mostly large positive cloud-to-ground lightning discharges. Since their discovery in the late 1980s, sprites have been observed extensively in other continents except in Africa, where there is little or no active sprites-related research. Despite the numerous observations of sprites to date, there is no conclusive study that has reviewed the electron energies and the strength of the electric field within sprites as a function of altitude. This thesis presents the _rst ground-based observations of sprites in southern Africa. These observations were conducted at the South African Astronomical Observatory, Sutherland, South Africa, during the austral summer of 2015/2016, 2016/2017 and 2017/2018, as well as at a site that is close to South African Square Kilometer Array, Carnarvon in 2017/2018. Sprites were observed using multiple cameras that were filtered at specific wavelengths. In 5 out of 65 nights of observations, 113 video frames containing one or more sprites were recorded, comprising different morphologies (Carrot-single (10%), Carrot/Column (10%), Carrot-groups (37%), Column-groups (12%), Tree-like (4%), Unclassified (23%), Jelly-fish (3%)). These events were between 429 to 890 km away from the observer. The error in this distance estimate was ±5% of the distance. During these observations, the cloud-top temperatures of the storms that initiated these events was about -58 degrees Celsius. Sprite events observed at specific wavelengths suggest that the first positive band of N2 dominates at the upper altitudes (around 65 km). By using the Maxwell-Boltzmann energy distribution function in collisional plasma, the average characteristic electron energies and the strength of the electric fields in sprites were estimated as 5.5 eV and 150 V/m respectively, which were comparable to those inferred from space-based observations. The charge moment change of the lightning strokes associated with the observed events agreed with the threshold for dielectric breakdown of the mesosphere and correlates well with the observed sprites brightness. The study also showed that the average detection rate for sprites in southern Africa was 0.14 sprites/minutes and that the carrot-shaped sprites are usually accompanied by an increase in the charged moment as compared to the columniform sprites.